Natural zeolite (chabazite/phillipsite) dietary supplementation influences faecal microbiota and oxidant status of working dogs. Issue 1 (2nd January 2017) - Superchi, Paola; Saleri, Roberta; Ossiprandi, Maria C.; Riccardi, Enzo; Passaglia, Elio; Cavalli, Valeria; Beretti, Valentino; Sabbioni, Alberto
Abstract: We evaluated whether chabazite/phillipsite dietary supplementation might affect the faecal microbiota, oxidant and antioxidant status of working dogs at rest undergone to a trial test. Forty English Setter dogs were involved in two replicate trials. At each replicate, dogs were divided into two homogeneous groups (10 dogs/group). During a period of 28 days, diet was supplemented (Z group) or not supplemented (C group) with chabazite/phillipsite at the dose of 5 g/head/day. On day 29, dogs were subjected to a trial test. Faecal characteristics were assessed at 0 and 29 days (within two hours from the end of the trial test). Faecal consistency was not affected by dietary supplementation ( p > .05). On day 29, Lactobacillus spp. and Enterococcus spp. counts were higher and Enterobacteriaceae were lower in Z than in C group ( p < .05). At day 0 and at day 29, immediately before and within one hour from the end of the trial test, blood samples were recorded to evaluate the oxidant and antioxidant status. A reduction of 40% in thiobarbituric acid reactive substances (TBARS) levels was observed in Z compared to the C group ( p < .05). Differences in nitric oxide and antioxidant enzymatic system levels were not significant ( p > .05). Our results suggest that chabazite/phillipsite dietary supplementation, improves the intestinal microbiota ecosystem and may counteract the oxidative damage caused by physical stress in hunting dogs at the beginning of the working season.